Optimization of The Development of Digital Teaching Materials Based on The Local Wisdom of Silek Pengudon Through the Anyflip Application in Primary Schools - Binti Mohd Syarif, Shuhaiza Binti Mohd Syarif; Sanches , Kathy; Eka Yulistranti, Amanda; Dewa Zulkhi, Muhammad (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2023)
This research is a type of development research and the model used is the 4D development model (Define, Design, Develop and Disseminate). This research was conducted at the 203/VI Rantau Panjang XII State Elementary School. This research data was obtained from media validation, language validation, material validation and practitioner validation. Apart from that, research data was also obtained from student response questionnaires as well as interviews and observations of Traditional Leaders, teachers and students. The results of this research show that the validation test from several expert assessments obtained a percentage of (1) media validation of 82.14% with very good criteria; (2) Language validation is 78.88% with good criteria; (3) material validation of 79.84% with good criteria; (4) practitioner validation was 76.81% with good criteria. Then it will be tested on students through a small group trial to see the readability of teaching materials based on the local wisdom of Silekpudon using the Anyflip application and the large group test received a student response rating of 89% with good criteria. Based on the research results, it can be concluded that the development of materials for the development of teaching materials based on local wisdom in Silek Penyudon using the Anyflip application in elementary schools can be used in learning at school.